Apakah Jenis Kelamin Memoderasi Pengaruh Harga Diri terhadap Perilaku Adiksi pada Instagram di Kalangan Remaja? - Indah Mulyani; Hera Lestari Mikarsa; Ira Puspitawati (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
Instagram is the most populer social media among adolescents today. Continously instagram usage can be potential to emerge addiction behavior. This study was aimed to test the effect of self-esteem to instagram addiction moderated by gender. Data were collected using the instagram addiction scale and self-esteem scale. The subjects were 27 adolescents, who previously amount 285, filtered through screening phase based on criteria individual with addiction according to DSM-V. Moderated regression analysis was used to test the hypothesis. Data analysis showed that self-esteem had a significant effect to instagram addiction (p<0.05), but not with gender. It said that both men and women have the same opportunities to engage in instagram addiction.